PERLINDUNGAN HUKUM TERHADAP HAK EKONOMI PEMEGANG PATEN NOKIA (KAJIAN INVENSI PATEN IDP000031184): Legal Protection For The Economic Rights Of Nokia As A Patent Holder (Study of Patent Invention IDP000031184) - Ashila Nawwafa Taqiya; Simona Bustani (Reformasi Hukum Trisakti, 2025)
The 2016 Patent Law Article 19 Paragraph (1) provides legal protection in the form of exclusive economic rights to patent holders, allowing them to gain economic benefits from their inventions. These rights include licensing to third parties in exchange for royalties. The use of patents beyond the licensing period without permission is considered a violation of the patent holder’s economic rights. This study examines the legal protection of Nokia’s economic rights for patents produced by Guangdong Oppo and Realme Chongqing and Nokia’s efforts to safeguard these rights. The research uses normative and descriptive methods with primary and secondary data analyzed qualitatively through deductive reasoning. The result and conclusion is the government provides patent holders with exclusive rights, including economic rights. Disputes arising from violations can be resolved through litigation or non-litigation. Nokia filed a compensation claim against PT Bright Mobile Telecommunication, but the claim was deemed inadmissible (niet ontvankelijk verklaard). Eventually, the matter was resolved through cross-licensing agreements with Guangdong Oppo and Realme Chongqing.